Dynamic modification of the fragmentation of autoionizing states of O2+ - Cao, W.; Laurent, G.; De, S.; Schöffler, M.; Jahnke, T.; Alnaser, A. S.; Bocharova, I. A.; Stuck, C.; Ray, D.; Kling, M. F.; Ben-Itzhak, I.; Weber, Th.; et al. (My University, 2011)
The dynamic process of fragmentation of excited states of the molecular oxygen cation is investigated in a two-part study. First, using monochromatic 41.6 eV radiation and cold-target recoil-ion momentum spectroscopy detection of O+ + O+ ion pairs and associated electrons, we establish that this channel is populated only by an indirect process enabled by autoionization of excited oxygen atoms and identify the final active potential curves. Second, we probe the dynamics of this process using an attosecond pulse train of 35–42 eV EUV followed by an intense IR laser pulse. The results are compared with a model calculation.